Konsep Kesejahteraan Sosial dalam Perspektif Ekonomi Islam - Nur Fadilah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
The Islamic economic sistem is not detached from the entire sistem of Islamic teachings in an integral and comprehensive. Thus, the basic principles of Islamic economics refer to the Islamic teachings. Conformity of the sistem with the human Fitrah is not left this alignment so that there is no collision in its implementation, the freedom of controlled economy into the character and principles of the Islamic economic sistem, freedom has Production elements in running the economy wheels are an important part of not harming collective interests. The interests of individuals are opened wide, the absence of income restrictions for a person encourages human beings to actively work with all its potential, the human tendency to continuously meet his or her own infinite needs in Control with the obligation of every individual to its community, the balance between individual and collective interests is this is a driving force for the wheels of the economy without damaging the existing social sistem. To realize social welfare has not fully fulfilled the ideal concept of social security within. Therefore, the author gives input that there needs to be an endeavor to realize the social welfare in accordance with Islamic economic objectives as well as human purpose itself. The endeavor must use the basic Islamic economy that is moral as the basis of the economic sistem, should keep the halal-haram in consumption, as well as the economy that aims to realize the welfare of mankind.